The Impact of Globalization on Market Access And Financial Technology Innovation: A Literature Review on Economic Legal Challenges and Regulatory Compliance - Purbiati, Ria; Khayatudin; Hasibuan, Ali Huristak Hartawan (Universitas Islam Negeri Alauddin Makassar, 2025)
Globalization has had a significant impact on the dynamics of the global financial market, particularly through the expansion of market access and the acceleration of financial technology (fintech) innovation. Cross-border economic integration has encouraged the transfer of knowledge, capital, and technology, resulting in more inclusive and efficient digital financial services. However, these developments have also brought about complex economic legal challenges and regulatory compliance issues. Differences in legal frameworks across countries, consumer protection, personal data policies, and the implementation of Anti-Money Laundering (AML) and Know Your Customer (KYC) principles are crucial factors influencing the success of fintech expansion internationally. This study uses a literature review method, examining academic literature, international reports, and relevant regulations to analyse the relationship between globalisation, market access, fintech innovation, and regulatory challenges. The findings indicate that optimising the benefits of globalisation in the fintech sector requires adaptive regulation, cross-border legal harmonisation, and strong international cooperation, enabling innovation to develop safely and equitably without compromising global financial stability.